(untitled) (Research, Society and Development, 2021)
The study aimed to evaluate the leathers of corvina and pescada amarela and tilapia. The hides were subjected to the tanning process with vegetable tannin and were evaluated by tensile strength and elongation tests, progressive tearing in the leather specimens, in addition to morphological and physical-chemical analysis, to ascertain the efficiency of the process and observe the behavior of the structure of collagen fibers after treatment. Among the samples, the tilapia leather showed lower mechanical strength, due to the histological architecture, as it presents a higher percentage of fine fibers about thick ones. The pescada amarela leather had more tensile strength (21.64 N/mm² in the transverse), greater elasticity in the transverse direction (105.60%), and greater tear resistance in the transverse direction (98.1 N/mm) and, corvina leather required less force in the transverse direction (59.83 N) compared to the longitudinal (86.50 N) even with less thickness. For the leather samples of the studied species, a low amount of oil in the fatliquoring was observed, observed by the analysis of extractable substances in dichloromethane, despite not having interfered in the resistance of these analyzed materials. The results were satisfactory for the leathers of the three species of fish, which can be applied for making clothing.